2017
DOI: 10.1177/1540796917697448
|View full text |Cite
|
Sign up to set email alerts
|

The Percentage of Supported Employees With Significant Disabilities Who Would Earn More in Sheltered Workshops

Abstract: This study examined the percentage of 21,257 supported employees served by 74 state-federal vocational rehabilitation agencies in 2013 who would have earned more wages in sheltered workshops than in the community. It found that the overwhelming majority of supported employees earned more in their communities at all wage comparison points; however, substantial differences in wages were identified according to the participant’s disability type, occupation, vocational rehabilitation agency, and the region in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…More than 50% of veterans with a polytrauma/traumatic brain injury find employment within three months of receiving SE regardless of additional challenges such as previous incarceration or homelessness (Pogoda et al, 2022). Transition age-youth with autism spectrum disorder who participate in an SE based internship program yield competitive employment outcomes ranging from 51% to 90% (Avellone et al, 2023;Christensen & Richardson, 2017;Christensen et al, 2015;Wehman, Schall et al, 2014;2017;Whittenburg et al, 2020). On average, employment outcomes for individuals with IDD who receive SE through Vocational Rehabilitation services is 7% higher than those who do not participate in SE (Chan & Kregel, 2019).…”
Section: Body Of Evidence For Supported Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50% of veterans with a polytrauma/traumatic brain injury find employment within three months of receiving SE regardless of additional challenges such as previous incarceration or homelessness (Pogoda et al, 2022). Transition age-youth with autism spectrum disorder who participate in an SE based internship program yield competitive employment outcomes ranging from 51% to 90% (Avellone et al, 2023;Christensen & Richardson, 2017;Christensen et al, 2015;Wehman, Schall et al, 2014;2017;Whittenburg et al, 2020). On average, employment outcomes for individuals with IDD who receive SE through Vocational Rehabilitation services is 7% higher than those who do not participate in SE (Chan & Kregel, 2019).…”
Section: Body Of Evidence For Supported Employmentmentioning
confidence: 99%
“…In addition to being more likely to obtain competitive work, those who receive SE services earn more money and work more hours than those who do not receive SE (Wehman, Taylor et al, 2020). The positive impact of SE on wage and hours has been observed among transition-age youth and adults with intellectual disability (Boeltzig et al, 2008;Cimera, 2017;Grossi et al, 2019;Iwanaga et al, 2023;Kregel et al, 1989;Seward, 2022;Wehman, 1986;Wehman et al, 1989), veterans with psychiatric disorders (Davis et al, 2022), adults with autism (Martin & Lanovaz, 2021), youth with autism (Whittenburg et al, 2020), and individuals with co-occurring mental illness and substance use disorders (Mueser et al, 2011).…”
Section: Body Of Evidence For Supported Employmentmentioning
confidence: 99%
“…Sheltered workshops were established after the Second World War to provide supported employment to recovering wounded or disabled soldiers (Slorach, 2016). Since then they have evolved as segregated organisational spaces for disabled workers and tend to specialise in manufacturing or general service (Cimera, 2017). Research on sheltered employment is often contentious focusing on their poor economic viability and the subsequent low employment success rate of the individuals who attend them (e.g.…”
Section: Sheltered Employmentmentioning
confidence: 99%
“…Current studies on sheltered organisations (e.g. Cimera, 2017) tend to focus on their economic performance, generally neglecting the deep understanding of the different forms of cultural and material support they provide to workers. This study focuses on a charity-based sheltered workshop operating in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…17 Even when people with ID are active in the labour market, their experience of employment differs from that of other workers. In particular, they are more likely to be in part-time work, 18 clustered in low status work, 19 and receiving low wages. 20 One US study found that people with Down Syndrome were frequently employed in restaurant/food services, office/clerical work, and cleaning/housekeeping.…”
Section: Labour Market Participationmentioning
confidence: 99%